Politics of Memory as a Tool of Civic Culture Formation: The Russian Specifics and Regional Aspects - Vodenko, Konstantin V.; Chernykh, Sergey S.; Ustimenko, Dmitry L.; Ustimenko, Alexei L. (Journal of History Culture and Art Research, 2020)
The purpose of the research is to describe the specifics of the formation of the discourse of politics of memory in Russia and to determine the means of its instrumentalization as applied to the processes of development of civic culture, aimed at unification of people around the common historical heritage. Regarding methodology, the potential of cultural & sociological approach, constructivism, the theory of social and symbolic capital, and inter-disciplinary analysis of monumental policy and its role in consideration of civic culture and creation of significant images of historical past is used. The authors dwell on the key directions in the spheres of studying the politics of memory in Russia as a tool of formation of civic culture in the context of global and regional trends; determine the specifics of politics of memory in Russia and define the state’s role in this process in view of the tendencies of formation of civic nation and unification around the common historical heritage; describe the complexities which might be faced by politics of memory in South of Russia – which are largely predetermined by the ethnocultural differences; consider further perspectives of development of research of politics of memory and civic culture in Russia within the influence of the “Eastern European discourse of memory” and other regional narratives.